A Novel Conformable Fractional Nonlinear Grey Bernoulli Model and Its Application. (19th September 2020) - Xie, Wanli; Yu, Guixian
Abstract : The fractional nonlinear grey Bernoulli model, abbreviated as FANGBM(1, 1), is a successful extension of NGBM(1, 1). Although FANGBM(1, 1) has numerous excellent characteristics, it has a more complex form of fractional accumulation (FA) operator than raw NGBM(1, 1). In this study, we propose a novel fractional nonlinear grey Bernoulli model, named CFNGBM(1, 1), which uses conformable fractional accumulation (CFA), which has a simpler form than FANGBM. Using two practical cases, the effectiveness of the proposed CFNGBM(1, 1) in practical applications was illustrated. Results show that the CFNGBM(1, 1) exhibited higher accuracy than other grey models, thus facilitating its promotion in engineering practices.